If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-1x + -1)(-13) = 0 Reorder the terms: (-1 + -1x)(-13) = 0 Reorder the terms for easier multiplication: -13(-1 + -1x) = 0 (-1 * -13 + -1x * -13) = 0 (13 + 13x) = 0 Solving 13 + 13x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 13x = 0 + -13 Combine like terms: 13 + -13 = 0 0 + 13x = 0 + -13 13x = 0 + -13 Combine like terms: 0 + -13 = -13 13x = -13 Divide each side by '13'. x = -1 Simplifying x = -1
| 8x+2=6x+42 | | tan^2x+3tanx=4 | | 17g-10=14g-20 | | 9y-5=2y+2 | | A-8.46=0 | | 3058375=5000000x+20000000 | | 2139516=5000000x+20000000 | | 2086560=5000000x+20000000 | | ((4x^2)+3x+7)(8x-5)=0 | | 1092922=5000000x+20000000 | | 1038105=5000000x+20000000 | | 1248278=5000000x+20000000 | | 100-100/100-100=2 | | 1/3=-7 | | ((7x^2)+9x+8)((9x^3)+7x)=0 | | X+(x+1)+10+1+2y=60 | | ((7x^2)+9x+7)(9x-4)=0 | | 1114812=4000000x+5000000 | | 1158205=4000000x+5000000 | | X+(x+1)+10=1+2y | | ((3x^2)+4x+4)(2x-4)=0 | | 928730=4000000x+5000000 | | 372265=4000000x+5000000 | | ((5x^3)-(4x^2)+6x+8)(9x+7)=0 | | -2-10x+1=-11x-10 | | 341788=4000000x+5000000 | | 458333=4000000x+5000000 | | (x+3)((3x^2)+8x+9)=0 | | 756565291=6000000x+20000000 | | ((5x^2)+5x+7)(8x+6)=0 | | 862201322=6000000x+20000000 | | 2X+X+2X=45 |